Comparison of the performance of the Panther Fusion respiratory virus panel to R-Gene and laboratory developed tests for diagnostic and hygiene screening specimens from the upper and lower respiratory tract. Issue 3 (2nd March 2020) - Ganzenmueller, Tina; Kaiser, Rolf; Baier, Claas; Wehrhane, Marlies; Hilfrich, Brigitta; Witthuhn, Jenny; Flucht, Sandra; Heim, Albert
Abstract : Introduction. Diagnosis of acute respiratory infections (ARIs) can be facilitated by the Panther Fusion (PF) automatic, random access PCR system for the detection of influenzavirus A (Flu A) and B (Flu B), parainfluenzavirus (Paraflu), respiratory syncytial virus (RSV), human metapneumovirus (hMPV), rhinovirus (RV) and human adenovirus (AdV) in nasopharyngeal swabs. Aim. To evaluate the performance of PF in comparison with established methods, including subsets of (1) lower respiratory tract (LRT) specimens and (2) upper respiratory tract (URT) hygiene screening specimens of patients without ARI symptoms. Methodology. The performance characteristics of PF were compared with bioMérieux R-Gene and laboratory-developed PCR tests (LDTs). Overall, 1544 specimens with 6658 individual diagnostic requests were analysed. Results. The overall concordances of PF and LDTs for Flu A, Flu B and AdV were 98.4, 99.9 and 96.1%, respectively; by re-testing of discrepant specimens concordances increased to 99.4, 99.9 and 98.0%, respectively. Initial concordances of PF and R-Gene assays for RSV, Paraflu, hMPV and RV were 98.4, 96.3, 99.3 and 96.0%, respectively, and retest concordances were 99.7, 97.9, 99.9 and 98.9%, respectively. No differences to the overall performance were found for the subgroups of LRT and hygiene screening specimens. PCR cycle threshold (Ct) values correlated very well between methods, indicating that a semi-quantitative diagnostic approach using Ct values (e.g. highly vs. weakly positive) could augment the diagnostic information. Conclusion. PF performed similar to R-Gene and LDTs not only for its intended use but also for LRT and hygiene screening specimens with shorter hands-on and turnaround times.